Acute Pancreatitis in Individuals with COVID-19: A Case Report and Critical Review of Literature - Arsia Jamali; Khashayar Nemovi; Betul N. Bayraktutar; Adam Farzaneh; Kevin Chan; Carlos Ramirez; Elika Shahkamrani; Anil Perumbeti (Case Reports in Medicine)
Involvement of gastrointestinal tract has been reported in individuals diagnosed with COVID-19. Herein, we report a case of 65-year-old woman with type 2 diabetes mellitus, hypertension, and end-stage renal disease undergoing hemodialysis who was initially diagnosed with COVID-19 on a screening test. During the course of the disease, her respiratory symptoms remained mild; however, she developed acute pancreatitis leading to severe hypertension and hyperosmolar hyperglycemic state. During the hospitalization and treatment of acute pancreatitis, hyperglycemia, and hypertension, her condition improved and she was discharged in stable condition.